Integrated Balanced Scorecard and DEA Approach for Performance Evaluation with Non-Discretionary Factors - Seyed Najafi; Mir Aryanezhad; Farhad Hosseinzadeh Lotfi; Seyyed Ebnerasoul (Big Data and Computing Visions)
Measuring the performance of production systems is a critical management task, which the Balanced Scorecard (BSC) framework addresses by providing a clear representation of key performance indicators across financial, customer, internal process, and learning and growth perspectives. In contrast, traditional data envelopment analysis (DEA) approaches evaluate systems holistically without considering individual processes. This paper presents an integrated BSC-DEA methodology that enables multi-criteria performance evaluation across different project stages. The integrated DEA-BSC model uses "cards" to group input and output measures associated with the BSC perspectives, enabling efficiency decomposition to identify specific processes causing system inefficiencies and inform future improvement efforts. The authors demonstrate the proposed integrated BSC-DEA framework through a case study involving six banking branches, providing a more comprehensive view of organizational performance compared to traditional approaches.